Indelible Images: New World Tattoos in Gonzalo Fernández de Oviedo’s Historia general (1535-1549) - Gansen, Elizabeth (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2024)
The Spanish historian Gonzalo Fernández de Oviedo (1478-1557) is one of the first Europeans to write about the tattoo as he observed it in the native societies of the Americas. In his attempts to understand this cultural phenomenon, he looks toward similar traditions overseas, namely Morisco tattoos and the practice of branding slaves. However, above all, Oviedo uses his knowledge of Spain’s courtly culture to interpret the function of the tattoo in the New World.